Membangun Kesadaran Orang Tua Dalam Motorik Halus Anak Usia 3-5 Di Kp. Bolong - Nurrohimah, Anisa; Mua’wanah, Uyu (JURNAL MANAJEMEN PENDIDIKAN, 2025)
BUILDING PARENTAL AWARENESS IN FINE MOTOR SKILLS OF CHILDREN AGED 3-5 IN KP. BOLONGFine motor development is a crucial aspect of early childhood development because it directly impacts academic ability, independence, and readiness for school activities. Skills such as grasping, writing, cutting, and stringing require good hand-eye coordination, so early stimulation is essential. However, initial observations in Kampung Bolong indicate that most parents do not yet understand the importance of providing fine motor stimulation at home. Lack of knowledge and limited time result in children receiving fewer activities that can hone these skills. This study aims to increase parental awareness and involvement through educational activities and practical guidance that emphasize sensory play and simple activities based on household materials, such as playing with plasticine, tearing paper, or moving small objects. This study used a descriptive qualitative approach using observation and interviews with ten parents of children aged 3–5 years. The results showed that 80% of participants experienced an increase in understanding and involvement in stimulating their children's fine motor development. Parents became more consistent in providing guidance and were able to create a variety of fun and educational daily activities. Furthermore, interaction between parents and children also increased, creating a more positive learning atmosphere at home. Based on these findings, this study recommends the need for ongoing community-based education programs to maintain parental awareness and participation in stimulating children's fine motor skills. Collaboration between early childhood education institutions and the community is crucial to creating an environment that supports optimal child growth and development.